ANALISIS MODEL KEMANFAATAN DAN KEMUDAHAN TEKNOLOGI DALAM MENGGUNAKAN APLIKASI E-LEARNING EDMODO - Tri Istining Wardani (Adbis: Jurnal Administrasi dan Bisnis, 2017)
The purpose of this study was to analyze the partial and simultaneous effect between Perceived of Usefulness (PU) and Perceived Ease of Use (PEU) toward the Student’s intention in utilizing e-learning Application Edmodo. The results : There is a simultaneous influence between the variables X consisting of Perception Usefulness (X1) and Perceived Ease (X2) toward variable The student’s intention to use e-learning Application Edmodo (Y). and it was found that the perception of usefulness variable (X1) did not has significant influence partially, instead Perceived Ease (X2) has significant influence partially on student intention in utilizing e-learning Application Edmodo (Y).